طرق تسوية المنازعات العامة في مجال الضمان الاجتماعي - عبد اللاوي, حنان (جامعة الوادي university el-oued, 2020)
لقد أوضح المشرع الجزائري منظومة قانونية متميزة للضمان الاجتماعي , وذلك بداية بصدور القانون83/15 وباقي القوانين المعدلة والمتممة له وصولا إلى القانون 08/08 , أوجد المشرع الجزائري وسائل وطرق قانونية لفك منازعات الضمان الاجتماعي ,حيث جاء في القانون 08/08 بآليات لتسوية المنازعات العامة للضمان الاجتماعي على درجتين: 1-التسوية الداخلية كدرجة أولى لحل المنازعات بطريقة ودية بين الأطراف ,وذلك من خلال اللجنة المحلية المؤهلة للطعن المسبق لقرارات هيئات الضمان الإجتماعي وهي نقطة البداية,وفي حالة عدم الرضا عن قرارات اللجنة المحلية يمكن للطرف المتضرر اللجوء إلى اللجنة الوطنية المؤهلة للطعن المسبق. 2-ثم أوضح اللجوء إلى التسوية القضائية كدرجة ثانية وذلك عند فشل المحاولات الودية أو التسوية الداخلية. وقد أوضح المشرع الجزائري في القانون08/08 كيفية اللجوء إلى المحكمة المختصة وأحال إجراءاتها ومواعيدها وطرق الطعن في قراراتها إلى القانون08/09 المتضمن قانون الإجراءات المدنية والإدارية. The Algerian legislation has put in place a distinct legal system of Social Security ,starting with the issuance of law 15/83 ,and the rest of the amended and supplemented laws,including the law08/08,and he has created legal means and methods for resolving Social Security disputes.In law 08/08 ,there are mechanisms for settling public Social Security disputes in two steps: 1-Internal Settlement as a first degree to settle disputes in a friendly manner between the parties,through the local committee that is qualified to advance appeal the decisions of the Social Security bodies,which is the starting point ,and in case of dissatisfaction with the decisions of the local committee,the affected party can resort to the National committee that is eligible for advance appeal. 2-Then he explained the resort to the judicial settlement as a second degee, when failure of the friendly attempts or the internal settlement. In the 08/08 law,the Algerian legislation explained how to resort to the competent court ,its procedures and deadlines,and ways to appeal its decisions to law 09/08 containing the civil and administrative procedures law
مذكرة ماستر
Keywords: المشرع.الضمان; The legislator. The guarantee